2014
DOI: 10.1038/nn.3615
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic glycine receptors as a potential therapeutic target for hyperekplexia disease

Abstract: While postsynaptic GlyRs as α/β heteromers attract the most research attention, little is known about the role of presynaptic GlyRs, likely α homomers, in diseases. Here, we demonstrate that DH-CBD, a nonpsychoactive cannabinoid, can rescue GlyR functional deficiency and exaggerated acoustic and tactile startle responses in mice bearing the point-mutations in the α1 GlyRs responsible for a hereditary startle/hyperekplexia disease. The GlyRs expressed as α1 homomers either in HEK-293 cells or at presynaptic ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 49 publications
(91 reference statements)
0
69
0
Order By: Relevance
“…Of interest was the observation that dehydroxyl-CBD (1μM) was more efficacious than CBD as it initiated a 9-fold increase in current amplitude. This observation led to the more recent study highlighting a role for dehydroxyl-CBD in modulating presynaptic GlyR and suggested a homomeric conformational bias for dehydroxyl-CBD effects [40].…”
Section: Glycine Receptorsmentioning
confidence: 97%
“…Of interest was the observation that dehydroxyl-CBD (1μM) was more efficacious than CBD as it initiated a 9-fold increase in current amplitude. This observation led to the more recent study highlighting a role for dehydroxyl-CBD in modulating presynaptic GlyR and suggested a homomeric conformational bias for dehydroxyl-CBD effects [40].…”
Section: Glycine Receptorsmentioning
confidence: 97%
“…For example, GlyRs are broadly expressed in brain (Lynch, 2009;Dutertre et al, 2012;Salling and Harrison, 2014) and are located extrasynaptically (Muller et al, 2008;Xu and Gong, 2010), presynaptically (Jeong et al, 2003;Xiong et al, 2014), and postsynaptically (Dumoulin et al, 2001), depending on the brain region and cell type studied. GlyRs from humans and rats contain three subtypes of a subunits (a1-3) and one b subunit (Grenningloh et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the a4 subunit is found in mice (Matzenbach et al, 1994) and chicks (Harvey et al, 2000). GlyRs in adult animals consist of heteromeric ab and homomeric a subunits (Lynch, 2009;Xiong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…20 These receptors are also expressed in the hippocampus [21][22][23][24][25] and in the cortex. 26,27 Importantly, GlyR heteromers cluster at the presynaptic membrane to control neurotransmitter release in the medial nucleus of trapezoid body in the brainstem, 28 the spinal cord 29,30 and the ventral tegmental area. 31 During neurogenesis, extrasynaptic GlyRs and their ligands are present in the forebrain 32,33 as well as in neurogenic regions of the postnatal brain.…”
mentioning
confidence: 99%